Human Double-Negative Regulatory T-Cells Induce a Metabolic and Functional Switch in Effector T-Cells by Suppressing mTOR Activity - Haug, Tabea; Aigner, Michael; Peuser, Moritz M.; Strobl, Carolin D.; Hildner, Kai; Mougiakakos, Dimitrios; Bruns, Heiko; Mackensen, Andreas; Völkl, Simon (Frontiers in Immunology, 2019)
The recently discovered population of TCRαβ+ CD4-/CD8- (double-negative, DN) T-cells are highly potent suppressor cells in mice and humans. In preclinical transplantation models, adoptive transfer of DN T-cells specifically inhibits alloreactive T-cells and prevents transplant rejection or Graft-versus-Host-disease (GvHD). Interestingly, clinical studies in patients who underwent allogeneic stem cell transplantation reveal an inverse correlation between the frequency of circulating DN T-cells and the severity of GvHD, suggesting a therapeutic potential of human DN T-cells. However, their exact mode of action has not been elucidated yet. Investigating the impact of DN T-cells on conventional T-cells, we found that human DN T-cells selectively inhibit mTOR signaling in conventional T-cells. Given that mTOR is a critical regulator of cellular metabolism, we further determined the impact of DN T-cells on the metabolic framework of conventional T-cells. Intriguingly, DN T-cells diminished expression of glucose transporters and glucose uptake, whereas fatty acid uptake was not modified, indicating that DN T-cells prevent metabolic adaptation of conventional T-cells upon activation (i.e. glycolytic switch) thereby contributing to their suppression. Further analyses demonstrated that conventional T-cells also do not upregulate homing receptors associated with inflammatory processes. In contrast, expression of central memory-cell associated cell surface markers and transcription factors were increased by DN T-cells. Moreover, CD4+ T-cells failed to produce inflammatory cytokines after co-culture with DN T-cells, whereas IL-2 secretion was enhanced. Taken together DN T-cells impair metabolic reprogramming of conventional T-cells by abrogating mTOR signaling, thereby modulating cell functionality. These results uncover a new mechanism of DN T cell mediated-suppression, pointing out that DN T-cells could serve as cell-based therapy to limit alloreactive immune response.